Impact of E-Training on the performance of employees at Safi Danon - Alshehri, Sameer Mohammed (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed at identifying the impact of E-Training on the performance of the employees of Safi Danon; To achieve this goal, the study adopted the survey descriptive curriculum. The study tool was a questionnaire form applied to a sample of 92 employees in Safi Danone’s sales department, to gather information about the questionnaire axes. The results of the study found the degree of utilization of E-Training on the performance of the employees of Safi Danone Company to a large extent, where the overall average came in equal (3.73) The degree of approval (consent), with a standard deviation of 1.12), the impact of E-Training on the process of performance development of the employees of Safi Danon in terms of sales skills came to a large extent, with the general average coming in equal to (3.85) and the degree of approval (agreed), with a standard deviation of 1.18), the impact of E-Training on the performance development process of the employees of SAFI Danon on the one hand came to a significant extent, with the averaging general being equal to (3.99) and the degree of approval (approved), with a standard deviation of 0.78. The study recommended the need to provide all the requirements for e-training, to provide competent trainers to train workers, and to motivate workers physically and morally to contribute to training.